Effects of combined nitrogen and phosphorus application on protein fractions and nonstructural carbohydrate of alfalfa - Zhao, Jiantao; Huang, Rongzheng; Wang, Xuzhe; Ma, Chunhui; Li, Man; Zhang, Qianbing (Frontiers in Plant Science, 2023)
Nitrogen (N) and phosphorus (P) fertilization significantly affect alfalfa production and chemical composition; however, the effect of combined N and P application on protein fractions and the nonstructural carbohydrate content of alfalfa is not fully understood. This two-year study investigated the effects of N and P fertilization on the protein fractions, nonstructural carbohydrates (NSC), and alfalfa hay yield. Field experiments were carried out using two nitrogen application rates (N60, 60 and N120, 120 kg N ha−1) and four phosphorus application rates (P0, 0; P50, 50; P100, 100; and P150, 150 kg P ha−1), total 8 treatment (N60P0, N60P50, N60P100, N60P150, N120P0, N120P50, N120P100 and N120P150). Alfalfa seeds were sown in the spring of 2019, uniformly managed for alfalfa establishment, and tested in the spring of 2021–2022. Results indicated that P fertilization significantly increased the hay yield (3.07–13.43% ranges), crude protein (6.79–9.54%), non-protein nitrogen of crude protein (fraction A) (4.09–6.40%), and NSC content (11.00–19.40%) of alfalfa under the same treatment of N application (p < 0.05), whereas non-degradable protein (fraction C) decreased significantly (6.85–13.30%, p < 0.05). Moreover, increasing N application resulted in a linear increase the content of non-protein N (NPN) (4.56–14.09%), soluble protein (SOLP) (3.48–9.70%), and neutral detergent-insoluble protein (NDIP) (2.75–5.89%) (p < 0.05), whereas acid detergent-insoluble protein (ADIP) content was significantly decreased (0.56–5.06%, p < 0.05). The regression equations for nitrogen and phosphorus application indicated a quadratic relationship between yield and forage nutritive values. Meanwhile, the comprehensive evaluation scores of NSC, nitrogen distribution, protein fractions, and hay yield by principal component analysis (PCA) revealed that the N120P100 treatment had the highest score. Overall, 120 kg N ha−1 coupled with 100 kg P ha−1 (N120P100) promoted the growth and development of perennial alfalfa, increased soluble nitrogen compounds and total carbohydrate content, and reduced protein degradation, thus improving the alfalfa hay yield and nutritional quality.